Factors Influencing Electronic Word of Mouth, Risk Perception, and Trust in the Intention to Purchase Computer Devices via Facebook Pages in Thailand - Thongchalerm, Silarpong; Lexcharoen, Somchai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This research aimed to: 1) develop and examine the goodness-of-fit of a causal relationship model of purchase intention for computer equipment on Facebook pages, and 2) investigate the direct and indirect influences affecting consumers' purchase intention for computer equipment on Facebook pages in Thailand. A quantitative research design was employed, using an online questionnaire as the research instrument. The sample consisted of 429 individuals who had previously purchased computer equipment through Facebook pages and resided in Thailand. Data were analyzed using frequency, percentage, confirmatory factor analysis, and structural equation modeling. The findings revealed that the developed causal relationship model comprised four dimensions: 1) electronic word-of-mouth, 2) perceived risk, 3) trust, and 4) purchase intention, and demonstrated a good fit with the empirical data. The factor with the greatest direct influence on purchase intention was perceived risk (β = 0.649), followed by electronic word-of-mouth and trust, respectively (β = 0.272). Business operators should therefore focus on reducing consumers' perceived risk in purchasing products or services, and foster active consumer engagement on Facebook pages, in order to enhance purchase intention for computer equipment through this platform.